Higher Order Thinking Skill: Teachers’ Perception and Their Assessment Implementation - Nyimas Larasati Utami (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: Higher order thinking skill (HOTS) is a required skill one needs to possess in this21st century. Without it, one can hardly compete with others in the world which increasingly demands critical thinking and creativity to solve problems. In teaching and learning process, the assessments towards HOTS are needed in order to make sure the skills are used effectively. This article highlights some issues of HOTS assessment. Firstly, the perception of the teachers regarding HOTS and its assessment is comprehensive but in practice, lower order thinking skills (LOTS) are more dominant in the assessment. Secondly, the factors challenging the teachers in constructing HOTS-based questions are categorized into teacher’s aspects, teaching and learning aspects, and student’s aspects. Lastly, the advantages of HOTS assessment for the students relate to how this type of assessment motivate students to learn as well as improve the learning outcomes. Keywords: Higher Order Thinking Skill (HOTS), assessment Abstrak: Kemampuan berpikir tingkat tinggi (HOTS) merupakan kemampuan wajib yang perlu dimiliki seseorang di abad ke-21 ini. Tanpanya, orang-orang akan kesulitan bersaing dengan orang lain dalam menjalani hidup yang menuntut pemikiran kritis dan kreatif dalam memecahkan masalah. Dalam proses belajar mengajar, diperlukan penilaian terhadap HOTS agar kemampuan tersebut digunakan secara efektif. Artikel ini menyoroti beberapa aspek yang berkaitan dengan penilaian kemampuan berpikir tingkat tinggi (HOTS). Pertama, persepsi guru tentang HOTS dan penilaiannya yang bersifat komprehensif namun dalam praktiknya muncul pertanyaan yang berbasiskan LOTS. Faktor-faktor yang menjadi tantangan guru dalam mengembangkan soal berbasis HOTS dikategorikan menjadi aspek guru, aspek belajar mengajar, dan aspek siswa. Manfaat penilaian HOTS bagi siswa adalah meningkatkan motivasi belajar siswa serta meningkatkan hasil belajar. Kata-kata kunci: Kemapuan berpikir tingkat tinggi, penilaian, HOTS